Mosaic pathogenic variants in AKT3 cause capillary malformation and undergrowth. Issue 5 (25th January 2023) - Bolli, Amber; Nriagu, Bede; Britt, Allison D.; Toole, Anjali D.; Treat, James; Srinivasan, Abhay; Sheppard, Sarah E.
Abstract: Capillary malformations are slow‐flow vascular malformations that affect the microcirculation including capillaries and post capillary venules and can be associated with growth differences. Specifically, the association of capillary malformations with undergrowth is a vastly understudied vascular syndrome with few reports of genetic causes including PIK3CA, GNAQ, and GNA11 . Recently, a somatic pathogenic variant in AKT3 was identified in one child with a cutaneous vascular syndrome similar to cutis marmorata telangiectatica congenita, undergrowth, and no neurodevelopmental features. Here, we present a male patient with a capillary malformation and undergrowth due to a somatic pathogenic variant in AKT3 to confirm this association. It is essential to consider that mosaic pathogenic variants in AKT3 can cause a wide spectrum of disease. There is a need for future studies focusing on capillary malformations with undergrowth to understand the underlying mechanism.